Infants with congenital nephrotic syndrome have comparable outcomes to infants with other renal diseases - ALPAY, HARİKA (SPRINGER, 2019)
BackgroundChildren with congenital nephrotic syndrome (CNS) commonly develop end stage renal failure in infancy and require dialysis, but little is known about the complications and outcomes of dialysis in these children.MethodsWe conducted a retrospective case note review across members of the European Society for Pediatric Nephrology Dialysis Working Group to evaluate dialysis management, complications of dialysis, and outcomes in children with CNS.ResultsEighty children (50% male) with CNS were identified form 17 centers over a 6-year period. Chronic dialysis was started in 44 (55%) children at a median age of 8 (interquartile range 4-14) months. Of these, 17 (39%) were on dialysis by the age of 6months, 30 (68%) by 1year, and 40 (91%) by 2years. Peritoneal dialysis (PD) was the modality of choice in 93%, but 34% switched to hemodialysis (HD), largely due to catheter malfunction (n=5) or peritonitis (n=4). The peritonitis rate was 0.77 per patient-year. Weight and height SDS remained static after 6months on dialysis. In the overall cohort, at final follow-up, 29 children were transplanted, 18 were still on dialysis (15 PD, 3 HD), 19 were in pre-dialysis chronic kidney disease (CKD), and there were 14 deaths (8 on dialysis). Median time on chronic dialysis until transplantation was 9 (6-18) months, and the median age at transplantation was 22 (14-28) months.ConclusionsInfants with CNS on dialysis have a comparable mortality, peritonitis rate, growth, and time to transplantation as infants with other primary renal diseases reported in international registry data.
Keywords: Congenital nephrotic syndrome; Infant dialysis; Complications; Outcome; CHRONIC DIALYSIS; PERITONEAL-DIALYSIS; CHILDREN; SURVIVAL; HEMODIALYSIS; EXPERIENCE; MANAGEMENT; MUTATIONS